2020
DOI: 10.2196/15099
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Segmentation to Explain the Online Health Information–Seeking Behavior of Older Adults: Representative Telephone Survey

Abstract: Background As a result of demographic changes, the number of people aged 60 years and older has been increasing steadily. Therefore, older adults have become more important as a target group for health communication efforts. Various studies show that online health information sources have gained importance among younger adults, but we know little about the health-related internet use of senior citizens in general and in particular about the variables explaining their online health-related informati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 46 publications
2
37
0
4
Order By: Relevance
“…These differences may be attributable to differences in health literacy, difficulties and frustration in accessing online information, or trust in health information from online sources [ 23 , 24 , 27 , 45 , 46 , 47 , 48 , 49 , 50 ]. Consistent with previous studies, we observed that older adults were also less likely to use the internet to locate health-related information for themselves or others [ 13 , 20 , 23 , 27 , 46 ]. Prior studies have observed that older individuals are more likely to access and trust health information from other sources, including friends and families and religious organizations [ 20 , 27 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be attributable to differences in health literacy, difficulties and frustration in accessing online information, or trust in health information from online sources [ 23 , 24 , 27 , 45 , 46 , 47 , 48 , 49 , 50 ]. Consistent with previous studies, we observed that older adults were also less likely to use the internet to locate health-related information for themselves or others [ 13 , 20 , 23 , 27 , 46 ]. Prior studies have observed that older individuals are more likely to access and trust health information from other sources, including friends and families and religious organizations [ 20 , 27 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studien zeigen, dass es einen Zusammenhang zwischen dem Gesundheitszustand und dem Gesundheitsinformationsverhalten älterer Menschen gibt. Manche deuten hierbei darauf hin, dass Personen mit gesundheitlichen Problemen -insbesondere in Form chronischer Erkrankungenmehr nach Gesundheitsinformationen suchen [14][15][16], während andere zeigen, dass Personen mit einem guten Gesundheitszustand häufiger Gesundheitsinformationen nutzen [12,17].…”
Section: Eine Wichtige Zielgruppe Bei äLterenunclassified
“…B. TV, Tageszeitung) heranziehen, um sich über Gesundheitsthemen zu informieren. Obwohl die Bedeutung des Internets als Gesundheitsinformationsquelle generell zunimmt [35][36][37], hat es für ältere Personen einen bisher eher geringen Stellenwert [12].…”
Section: Fazit Und Ausblickunclassified
See 2 more Smart Citations